2012
DOI: 10.1002/mbo3.49
|View full text |Cite
|
Sign up to set email alerts
|

Extragenic suppressor mutations that restore twitching motility to fimL mutants of Pseudomonas aeruginosa are associated with elevated intracellular cyclic AMP levels

Abstract: Cyclic AMP (cAMP) is a signaling molecule that is involved in the regulation of multiple virulence systems of the opportunistic pathogen Pseudomonas aeruginosa. The intracellular concentration of cAMP in P. aeruginosa cells is tightly controlled at the levels of cAMP synthesis and degradation through regulation of the activity and/or expression of the adenylate cyclases CyaA and CyaB or the cAMP phosphodiesterase CpdA. Interestingly, mutants of fimL, which usually demonstrate defective twitching motility, freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Notably, CpdA homologs of V. cholerae [56] and P. aeruginosa are required for colonization efficiency and regulation of twitching-motility and virulence factors [53], [57], [58], respectively. The stringent control of cAMP levels is important in a wide variety of bacterial behaviors, thus we hypothesized that cAMP-PDEs could have an uncharacterized role in mediating other pathogenesis-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CpdA homologs of V. cholerae [56] and P. aeruginosa are required for colonization efficiency and regulation of twitching-motility and virulence factors [53], [57], [58], respectively. The stringent control of cAMP levels is important in a wide variety of bacterial behaviors, thus we hypothesized that cAMP-PDEs could have an uncharacterized role in mediating other pathogenesis-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…FimL, FimV, and PilG are all required for activation of CyaB, with FimL proposed to link FimV to the Chp system through PilG (17,22,32,33). However, while phenotypes associated with fimL deletion could be rescued by deletion of cpdA or by increasing intracellular cAMP levels in other ways (22,33,34), provision of exogenous cAMP failed to restore motility to a pilG mutant (17). We investigated whether the cAMP-independent function of PilG also required FimV by comparing PilU levels-a proxy for intracellular cAMP levels (21, 25)-twitching, and piliation in fimL, fimV, and pilG single mutants or in double mutants also lacking cpdA to prevent the degradation of endogenous cAMP (33) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, FimL's role in twitching is limited to its ability to connect PilG and FimV, leading to CyaB activation via an as-yet-unknown mechanism. Interestingly, Nolan et al (34) identified other suppressors of fimL that mapped outside the cyaA, cyaB, pilG, pilH, vfr, and cpdA loci. How those uncharacterized loci fit into the FimV-FimL-PilG signaling axis remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…FimL, FimV, and PilG are all required for activation of CyaB, with FimL proposed to link FimV to the Chp system through PilG (17, 22, 31, 32). However, while phenotypes associated with fimL deletion could be rescued by deletion of cpdA or by increasing intracellular cAMP levels in other ways (22, 32, 33), provision of exogenous cAMP failed to restore motility in a pilG mutant (17). We investigated whether the cAMP-independent function of PilG also required FimV by comparing PilU levels – a proxy for intracellular cAMP levels (21, 25) – twitching, and piliation in fimL , fimV , and pilG single mutants or in double mutants also lacking cpdA to prevent degradation of endogenous cAMP (32) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, FimL's role in twitching is limited to its ability to connect PilG and FimV, leading to CyaB activation via an as-yet unknown mechanism. Interestingly, Nolan et al (33) identified other suppressors of fimL that mapped outside the cyaA , cyaB , pilG , pilH , vfr , and cpdA loci. How those uncharacterized loci fit into the FimV-FimL-PilG signalling axis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%